(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Determination of the calorific values and elemental contents of plant biomass are important in considering their heat energy potential and environmental friendliness. It is also important in performance modelling calculations on thermal systems. This study measures the calorific values of twenty (20) biomass comprising herbaceous plants and agricultural waste with the aim of understanding their energy potential to be used as alternative fuels for small-scale industrial and domestic heating activities. The direct measurements of the calorific values were made using Bomb calorimeter (model 6100 series) and estimated from the ultimate analysis data of the samples. The relationships between the calorific value and the total carbon and hydrogen contents of samples were also investigated. The analysis results indicate that palm kernel shell and locust bean pod have the highest energy values of 41.1165 MJ/kg and 36.2230 MJ/kg respectively. Camel foot and soybean stalks give the lowest energy values of 6.0484 MJ/kg and 5.3353 MJ/kg respectively. The energy values of about 60% of biomass samples are in the range of 15-21 MJ/kg in agreement with the widely reported values in the literature. Further analysis indicates that the experimental measurements do not excellently agree with the values estimated using correlation equations and, in most cases, the experimental data is higher than that estimated using correlation equations. However, about 60% of the data points computed using the two equations agree closely. The study shows that the calorific values of all samples are strong function of their total carbon contents and have no...